On the Dirac equation with PT-symmetric potentials in the presence of position-dependent mass - Castro, L.B. (Physics letters. A, 2011)
The relativistic problem of fermions subject to a PT-symmetric potential in the presence of position-dependent mass is reinvestigated. The influence of the PT-symmetric potential in the continuity equation and in the orthonormalization condition are analyzed. In addition, a misconception diffused in the literature on the interaction of neutral fermions is clarified. ► The quadricurrent is not conserved for PT-symmetric potentials. ► The orthonormal condition is consistent depending on the suitable boundary condition. ► A misconception on the interaction of neutral fermions is clarified.